Physicochemical water quality and basic soil parameters of Embung B, Institut Teknologi Sumatera: a preliminary assessment - Cindy Moyna Clara LA; Reyhan Puji Putranto; Fatma Fitriyah; Yeni Fingky Claudia Purba; Silvia Rachmadani Putri; Nirmala Mustika Putri; Sherlita Aprianti Simanjuntak; Elisabet Sihotang; Muhamad Allan Serunting (Scientific Nexus, 2025)
This study evaluated the water quality of Embung B by analyzing samples collected from three locations for pH, conductivity, total dissolved solids (TDS), total suspended solids (TSS), and Fe(III) concentrations. TDS and TSS were determined using gravimetric methods, while Fe(III) was quantified colorimetrically via the Fe(SCN)²⁺ complex at 480 nm. TDS values measured with a water quality meter were compared to gravimetric results to examine methodological differences. The pH ranged from 8.31 to 8.83, within the permissible range of 6–9. Conductivity values indicated low ionic content, reflecting minimal particulate matter. Gravimetric TDS ranged from 244 to 39,844 ppm, while meter readings were lower, highlighting method-dependent variation. Fe(III) concentrations were 0.241, 0.230, and 0.178 ppm, all below the national limit of 0.3 ppm for drinking water. According to the pollution index, Embung B is classified as lightly polluted but remains within acceptable ecological conditions. Overall, Embung B exhibits stable water quality, low suspended solids, and safe Fe(III) levels, with pH within regulatory limits. Despite variations in TDS measurements, the reservoir is suitable for environmental and educational purposes. Regular monitoring is recommended to maintain long-term ecological integrity and sustainable management.